Outcome of treatment of vulvodynia by local application of anaesthetic agent - Gupta, Pratiksha; Shekhar, Chandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Vulvodynia is a chronic gynecological disorder. It has a widespread effect on quality of life due to physical disabilities, psychological distress and sexual dysfunction. The objective of the study was to assess the effectiveness of application of 5% Xylocaine ointment for treatment of Vulvodynia. Methods: This prospective study was conducted in the department of Obstetrics and Gynecology in Government Medical College and Hospital Chandigarh, from November 2004 to October 2010. Study included 520 female patients (age range, 20–65 years; mean, 32.50 years) with the diagnosis of Vulvodynia. Vulvodynia was measured by using Friedrich criteria. Daily and intercourse related pain was measured using a 10-mm visual analogue scale. Comparison was done between ability to have intercourse and pain ratings before and after the treatment. Results: After a mean of 8 weeks’ treatment, the daily pain rating was 10.37 points lower as compared to pretreatment phase. The intercourse-related pain score was 39.11 points lower after treatment. After six months of follow-up, eighty-eight percent (458/520) of women reported ability to have intercourse after treatment compared with 34% 177/520) at the initial visit. Visual analogue score of 520 patients were significantly reduced from 8.6 to 2.5 after post treatment. Conclusions: Topical 5% Xylocaine ointment was associated with an improvement in symptoms in the majority of women with Vulvodynia.